Meta-Research: How parenthood contributes to gender gaps in academia - Zheng, Xiang; Yuan, Haimiao; Ni, Chaoqun (eLife, 2022)
Being a parent has long been associated with gender disparities in academia. However, details of the mechanisms by which parenthood and gender influence academic career achievement and progression are not fully understood. Here, using data from a survey of 7,764 academics in North America and publication data from the Web of Science, we analyze gender differences in parenthood and academic achievements and explore the influence of work-family conflict and partner support on these gender gaps. Our results suggest that gender gaps in academic achievement are, in fact, “parenthood gender gaps.” Specifically, we found significant gender gaps in most of the measures of academic achievement (both objective and subjective) in the parent group but not in the non-parent group. Mothers are more likely than fathers to experience higher levels of work-family conflict and to receive lower levels of partner support, contributing significantly to the gender gaps in academic achievement for the parent group. We also discuss possible interventions and actions for reducing gender gaps in academia.
Keywords: meta-research; gender gap; academic career; parenthood; work-family conflict; partner support